Parametric analysis efficiency screen-vacuum thermal insulation of regenerative heat exchanger heat loss recovery system mobile compressor plant - G. I. Chernov; V. L. Yusha; A. M. Kalashnikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this work, a study is conducted of the effectiveness of the screen-vacuum thermal insulation of the heat exchanger of the heat loss recovery system of a mobile compressor unit using the method of its calculation developed on the basis of the Ansys package (Fluid Flow — Fluent). According to the results of the numerical analysis of working processes in the flow part of the shell-and-tube recuperative heat exchanger, the interrelation between the parameters of thermal insulation and the characteristics of the heat exchanger has been established